DNA Damage Sensor γ-H2AX Is Increased in Preneoplastic Lesions of Hepatocellular Carcinoma - Yasunobu Matsuda; Toshifumi Wakai; Masayuki Kubota; Mami Osawa; Masaaki Takamura; Satoshi Yamagiwa; Yutaka Aoyagi; Ayumi Sanpei; Shun Fujimaki (The Scientific World Journal)
Background. Phosphorylated histone H2AX (γ-H2AX) is a potential regulator of DNA repair and is a useful tool for detecting DNA damage. To evaluate the clinical usefulness of γ-H2AX in hepatocellular carcinoma (HCC), we measured the level of γ-H2AX in HCC, dysplastic nodule, and nontumorous liver diseases. Methods. The level of γ-H2AX was measured by immunohistochemistry in fifty-eight HCC, 18 chronic hepatitis, 22 liver cirrhosis, and 19 dysplastic nodules. Appropriate cases were also examined by fluorescence analysis and western blotting. Results. All cases with chronic liver disease showed increased levels of γ-H2AX expression. In 40 (69.9%) of 58 cases with HCC, the labeling index (LI) of γ-H2AX was above 50% and was inversely correlated with the histological grade. Mean γ-H2AX LI was the highest in dysplastic nodule (74.1±22.1%), which was significantly higher than HCC (P<0.005). Moreover, γ-H2AX was significantly increased in nontumorous tissues of HCC as compared with liver cirrhosis without HCC (62.5±24.7%, from 5.1 to 96.0%, P<0.005). Conclusions. γ-H2AX was increased in the preneoplastic lesions of HCC and might be a useful biomarker for predicting the risk of HCC.